Catalytic Dibenzocyclooctene Synthesis via Cobalt(III)–Carbene Radical and ortho‐Quinodimethane Intermediates - te Grotenhuis, Colet; van den Heuvel, Naudin; van der Vlugt, Jarl Ivar; de Bruin, Bas (Angewandte Chemie International Edition, 2018)
The metalloradical activation of ortho‐benzallylaryl N‐tosyl hydrazones with [Co(TPP)] (TPP=tetraphenylporphyrin) as the catalyst enabled the controlled exploitation of the single‐electron reactivity of the redox non‐innocent carbene intermediate. This method offers a novel route to prepare eight‐membered rings, using base metal catalysis to construct a series of unique dibenzocyclooctenes through selective Ccarbene−Caryl cyclization. The desired eight‐membered‐ring products were obtained in good to excellent yields. A large variety of aromatic substituents are tolerated. The proposed reaction mechanism involves intramolecular hydrogen atom transfer (HAT) to CoIII–carbene radical intermediates followed by dissociation of an ortho‐quinodimethane that undergoes 8π cyclization. The mechanism is supported by DFT calculations, and the presence of radical‐type intermediates was confirmed by trapping experiments. Metalloradical activation of the shown N‐tosyl hydrazones with [Co(TPP)] provides an effective method for the construction of a series of unique dibenzocyclooctenes in good to excellent yields. The proposed reaction mechanism involves intramolecular hydrogen atom transfer to the key CoIII–carbene radical followed by dissociation of an ortho‐quinodimethane, which then undergoes 8π cyclization.